Suicide Attempt and Suicidal Drug Overdose in Chronic Obstructive Pulmonary Disease Patients With or Without Depression - Lin, Chi-Yu; Harnod, Tomor; Lin, Cheng-Li; Kao, Chia-Hung (Frontiers in Psychiatry, 2020)
Background: To determine differences in the incidence and risks of suicide attempt (SA) and suicidal drug overdose (SDO) between chronic obstructive pulmonary disease (COPD) patients with and without comorbid depression by using data from Taiwan’s National Health Insurance Research Database. Methods: We analyzed the data of patients aged ≥20 years who had received a COPD diagnosis between 2000 and 2012. These COPD patients were divided into those with and without depression, and they were compared against a cohort from the general population. We calculated adjusted hazard ratios and the corresponding 95% confidence intervals for SA and SDO in the 3 cohorts after adjustment for age, sex, and comorbidities. Results: Until the end of 2012, 5.81% of patients with COPD developed depression. The incidence of SA and SDO in COPD patients with and without depression was 29.7 and 4.69 per 10 000 person-years and 71.2 and 20.9 per 10 000 person-years, respectively. COPD patients with depression had 13.6- and 10.0-fold higher risks of SA and SDO, respectively, than did controls. Particularly, an increased risk of SA caused by the enhancement effects of depression on COPD was noted in patients aged less than 50 years. Conclusion: SA and SDO risks are extremely high in Taiwanese COPD patients with depression. Our findings suggest that clinicians should be aware that for COPD patients with comorbid depression, prescribing a large amount of medications may be associated with SA risk through SDO.